SMALL DOMESTIC’ WRECKS: CHRONICLES OF FAMILY’ LIFE IN THE WORKS OF GERMÁN DEHESA’ (Andamios, Revista de Investigación Social, 2011)
Summary: This essay traces the genealogy of Germán Dehesa’s work along the border of journalism and literature —an extension of 19thcentury costumbrismo and an instance of 20-century chronicle— and analyzes its formal and thematic peculiarities. Through the lens of humor, Dehesa’s work focuses on the everyday life of middle-class families and strives to outline a new form of fatherhood, whose emergence in history is recent and whose record in Mexican literature is scarce.
Keywords: Chronicle; family; humor; customs; fatherhood